Bangun Alat Filtrasi dan Sterilisasi Ultraviolet dengan Sistem Kontrol Otomatis Berbasis Arduino Uno - Sujono Sujono; Arjuna Andriyanto Cahyo Nugroho (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
The cultivation of fish very kualtas on water , the quality of water found in degrees pH or acidity that is on the water .A quality of water that can cause bad fish arwana stress and make dead fish .Check the quality of water still relies on human resources and is still done manually by using paper pH . From trouble the writers will make a monitoring the quality of water to determine the value of water accurately pH .It uses a PH probe to read voltage water will be converted into pH values .Module PH-4502c to convert voltage pH obtained from pH probe into pH values .The data pH to be seen to lcd 12x6. Furthermore, when the pH value exceeds the pond water level limit for fish, the relay will run the filter pump and turn on ultraviolet to stabilize the water's pH value. The results of implementing a microcontroller using Arduino obtained a stable value for the pH content in the pool. Based on tests that have been carried out for 1 week, the results of calculating the percentage of effectiveness using ultraviolet filtration and sterilization equipment, by calculating ammonia in pools that use the equipment and those that do not, obtained a value of 91% to reduce anomiac, which aims to stabilize the pH of the air to obtain pool air quality.